Methodology for altering omega-3 EPA+DHA and omega-6 linoleic acid as controlled variables in a dietary trial. Issue 6 (June 2021) - MacIntosh, Beth A.; Ramsden, Christopher E.; Honvoh, Gilson; Faurot, Keturah R.; Palsson, Olafur S.; Johnston, Angela D.; Lynch, Chanee; Anderson, Paula; Igudesman, Daria; Zamora, Daisy; Horowitz, Mark; Gaylord, Susan; et al.
Summary: Background & aims: Increasing dietary intake of n-3 EPA+DHA and lowering dietary n-6 LA is under investigation as a therapeutic diet for improving chronic pain syndromes as well as other health outcomes. Herein we describe the diet methodology used to modulate intake of n-3 and n-6 PUFA in a free living migraine headache population and report on nutrient intake, BMI and diet acceptability achieved at week 16 of the intensive diet intervention and week 22 follow-up time-point. Methods: A total of 178 participants were randomized and began one of three diet interventions: 1) a high n-3 PUFA, average n-6 PUFA (H3) diet targeting 1500 mg EPA+DHA/day and 7% of energy (en%) from n-6 linoleic acid (LA), 2) a high-n-3 PUFA, low-n-6 PUFA (H3L6) targeting 1500 mg EPA+DHA/day and <1.8 en% n-6 LA or 3) a Control diet with typical American intakes of both EPA+DHA (<150 mg/day) and 7 en% from n-6 LA. Methods used to achieve diet change to week 16 include diet education, diet counseling, supply of specially prepared foods, self-monitoring and access to online diet materials. Only study oils and website materials were provided for the follow-up week 16 to week 22 periods. Diet adherence was assessed by multiple 24 h recalls administered throughout the trial. Diet acceptability was assessed in a subset of participants at 4 time points by questionnaire. Results: At week 16 H3 and H3L6 diet groups significantly increased median n-3 EPA+DHA intake from 48 mg/2000 kcals at baseline to 1484 mg/2000 kcals (p < 0.0001) and from 44 mg/2000 kcals to 1341 mg/2000 kcals (p < 0.0001), respectively. In the Control group, EPA+DHA intake remained below the typical American intake with baseline median at 60 mg/2000 kcals and 80 mg/2000 kcals (p = 0.6) at week 16. As desired, LA intake was maintained in the H3 and Control group with baseline median of 6.5 en% to 7.1 en% (p = 0.4) at week 16 and from 6.5 en% to 6.8 en% (p = 1.0) at week 16, respectively. In the H3L6 group, n-6 LA decreased from 6.3 en% at baseline to 3.2 en% (p < 0.0001) at week 16. There were no significant changes in BMI or diet acceptability throughout the trial or between diet groups. Conclusions: We find this diet method to be acceptable to research participants and successful in altering dietary n-3 EPA+DHA with and without concurrent decreases in n-6 LA. If n-6 LA of less than 3 en% is desired, additional techniques to limit LA may need to be employed.